THE INFLUENCE OF PRICE PERCEPTIONS, PRODUCT REVIEWS, AND CONVENIENCE ON PURCHASE DECISIONS AT TOKOPEDIA E-COMMERCE - Citaningtyas Ari Kadi, Dian; Ula Ananta Fauzi, Rizal; Ahmad, Arman Hj.; Putri Wardani, Winda (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2023)
This study is entitled "The Influence of Price Perception, Product Reviews, and Ease of Purchasing Decisions on E-Commerce Tokopedia in Madiun City." This study aimed to determine the effect of price perceptions, product reviews, and convenience on purchasing decisions on e-commerce Tokopedia in Madiun City. This quantitative research uses a sampling technique using probability sampling with a simple random sampling technique. The respondents of this study were 384 people—data analysis using multiple linear regression using the SmartPLS 3.0 application. Based on the results of hypothesis testing, there is a positive and significant effect between price perceptions and purchasing decisions, a positive and significant effect between product reviews and purchasing decisions, and a positive and significant influence between convenience and purchasing decisions. However, the perception of price, product reviews, and convenience do not simultaneously affect purchasing decisions.